2022
DOI: 10.1002/rmb2.12484
|View full text |Cite
|
Sign up to set email alerts
|

The morphokinetics algorithm based on data from day 5 blastocyst transfer (KIDScoreD5 version 3) is also useful for embryo selection in day 6 blastocyst transfer

Abstract: Purpose To analyze whether the morphokinetics algorithm based on data from day 5 blastocyst transfer (KIDScoreD5 version 3) can predict the pregnancy rate of both day 5 and day 6 blastocyst transfers. Methods The relationship between KIDScoreD5 and clinical pregnancy rate was evaluated using the Cochran–Armitage test and receiver‐operating characteristic (ROC) curve analysis. Results A positive correlation was observed between the KIDScoreD5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Overall, our study agrees with published data that have shown that both morphologic and morphokinetic parameters have a role in selecting blastocyst embryos for transfer [ 3 , 6 , 16 , 17 ] and even on day 3 can predict embryo competence. [ 7 , 8 ] However, when comparing morphologic to morphokinetic parameters on day 3, the expertise of an embryologist was superior to the morphokinetic model with an AUC closer to 1 (0.66 vs. 0.58 respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our study agrees with published data that have shown that both morphologic and morphokinetic parameters have a role in selecting blastocyst embryos for transfer [ 3 , 6 , 16 , 17 ] and even on day 3 can predict embryo competence. [ 7 , 8 ] However, when comparing morphologic to morphokinetic parameters on day 3, the expertise of an embryologist was superior to the morphokinetic model with an AUC closer to 1 (0.66 vs. 0.58 respectively).…”
Section: Discussionsupporting
confidence: 92%